GAMBARAN POLA TIDUR PADA IBU HAMIL PRIMIGRAVIDA TRIMESTER III - Fitriyani, Tanti; Rudatiningtyas, Ulfa Fadilla; Lestari, Tri Endah Widi (STIKes Bina Cipta Husada, 2024)
The sleep pattern is a habit of falling asleep until wake up who is experienced in pregnant women. During pregnancy change in sleep patterns due to feelings of anxiety, and the onset of various health problems such as back pain, frequent urination, nausea and dizziness that often occur at night are very influential on sleep patterns of pregnant women. The purpose of this study is to investigate the characteristics of pregnant women, sleep patterns based on the position, bedtime rituals, the sleep duration of sleep per day, and rest sleep disorders in third trimester primigravidae. The study design was descriptive type. The sample in this study used total population with 33 third trimester primigravida women as the respondents. Instruments used questionnaire with 16 questions. Analysis of the data used frequency and percentage distributions. From the results obtain that most of pregnant women choose aslant position to the left as many as 20 respondents 60,6%, ritual before going to sleep in most of pregnant women many as 21 respondents (63,65%) majority of respondents watching TV as many as nine respondents (27,3%), total sleep duration day during pregnancy, mostly of respondents sleep 6-8 hours as many as 24 respondents (72,7%), and most of the respondents experienced mild rest sleep disorder that is as many as 19 respondents (57,6%). Suggestions in this study are expected that pregnant women follow counselling about sleep patterns given by health workers, while for researchers to conduct further research on other factors that could affect sleep patterns in pregnant women.